Pemanfaatan Batu Kapur Dan Tempurung Kelapa Dalam Pengolahan Limbah Detergen - Jasman Jasman; Anselmus Kabuhung (Jurnal Kesehatan Lingkungan, 2020)
Disposing of detergent waste into water bodies, both rivers and sea will affect biota in water, as the results of stated that the effect of laundry waste on nila mortality has a significant influence and differences in each concentration. A research on the design of appropriate technology for processing laundry waste (detergent) is required by using a combination of limestone and coconut shell filter media. The purpose of this study was to determine the ability of limestone and coconut shell filter media to reduce detergent content, pH and TSS in wastewater. Quasi-experimental research methods with pre-test and post test design. Population and research samples are waste taken from laundry waste. The research data will be analyzed univariately in a descriptive and bivariate form with statistical analysis using the T-test. The results of the study laundry processing (detergent) using limestone and coconut shell media can reduce the content of detergents (39.75% - 67.14%), pH (0.89% - 4.68%) and TSS (0.00% - 96.72%). T test results show that there are very significant differences before and after treatment, meaning that waste treatment can reduce the content of detergents in laundry wastewater.